Bancarización en las instituciones bancarias en la región Loreto, periodo 2016 - 2020 - Gonzales Honores, Anthony (2022)
Banking for its growth is based on the decrease in informality, the behavior of the different economic sectors, the dynamics of the region's economy; but also, how much do the institutions involved in financial education do. The research aims to analyze banking in the Loreto region in the period 2016 - 2020, it is an applied research of descriptive level and non-experimental design; To analyze banking, we worked only with the deposits and credits granted by the different institutions involved and the Gross Domestic Product referenced through the Gross Added Value in each period analyzed. The results conclude that the banking rates in the Loreto region are low, in deposits they only reached 18% in the 2020 period and the lowest is in 2017 with 11.25%; In loans, the banking index is slightly higher than deposits, in 2020 it reached 23.29% and the lowest is reflected in 2018 with 20.70%.